Objective and subjective socioeconomic status associated with metabolic syndrome severity among African American adults in Jackson Heart Study. (July 2020) - Cardel, Michelle I.; Guo, Yi; Sims, Mario; Dulin, Akilah; Miller, Darci; Chi, Xiaofei; Pavela, Gregory; DeBoer, Mark D.; Gurka, Matthew J.
Highlights: Lower perception of rank in US society showed greater MetS severity at baseline. Social rank perception may be a stronger predictor of MetS severity in women relative to men. Subjective social status is important to consider when exploring social determinants in health. Abstract: Purpose: To assess independent associations between objective socioeconomic status (OSS) and subjective social status (SSS) with metabolic syndrome (MetS) severity and indicators among African American (AA) adults in the Jackson Heart Study (JHS) at baseline (2000–2004) and eight-year follow-up (2009–2013). Methods: Participants included 1724 AA adults from the JHS cohort (64.4 % women; mean age 53.4 ± 11.8). Associations of OSS (annual household income and school years completed) and SSS (measured with MacArthur Scales) with sex- and race/ethnic-specific MetS severity Z-score were examined after adjustment for demographics and MetS risk factors (i.e., nutrition, physical activity, smoking status, alcohol consumption, and depressive symptoms) at baseline and eight-year follow-up. Principal results: Independent of OSS, demographic, psychosocial, and lifestyle factors, individuals with lower US-society SSS had more severe MetS at baseline. A significant interaction existed between sex and US-society SSS such that women with lower perceived social status had more severe MetS severity at baseline, and for every one unit increase in US-society SSS, MetS severity Z-score is estimated to decrease by 0.04. Components of MetS driving the relationship between US-society SSS and MetS severity at baseline were the inverse associations of SSS with glucose levels and the positive associations of SSS with HDL-C. Physical activity was independently associated with MetS severity at baseline, but not at eight-year follow-up. Major conclusions: Though subjective and objective measures of social status are independently associated with cardiometabolic risk factors and MetS severity among AA adults, SSS may be a stronger predictor of MetS severity than OSS, particularly among women. SSS should be considered in conjunction with OSS when exploring social determinants of cardiometabolic health.